(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
Prostitution is a social phenomenon common in several civilizations. Although it is sustained by the society and its components, it is also discriminated by it as a profession, which results in several punishments to the prostitutes. The objective of this study was to investigate contingencies that maintain the behavior of prostitution, denying from the start internal causes like “character”, and focusing on the relation between the prostitute and her environment. It was considered prostituting behavior the act of maintaining sexual relations with a client in exchange for money. Contingences of reinforcement or aversive ones involved in the behavior of prostitution were verified. The analysis was based on the verbal report of six prostitutes from different work places and the assessment is founded over the principles of behavior analysis. It was noticed as maintaining contingencies: avoidance of a worst situation, imitation, generalized reinforcement, immediate reinforcement, primary reinforcement, among other factors. Another noticeable aspect was that the work’s aversive stimulation does not control the behavior when in competition with the reinforcements mentioned, probably because it is delayed and gradually introduced.